Implementation of learning methods in practical field experience (PPL) in english language subjects at SMP swasta HKBP Batu 4 - Novita Gresiana Manurung; Herman Herman; Sahat Renol HS; Esti Marlina Sirait (Abdimas Paspama, 2024)
This article aims to discuss the results of practical field experience (PPL) by prospective teachers (students) in implementing micro teaching courses as part of their studies. The Field Experience Practice Program (PPL) at HKBP Batu 4 Private Middle School, will be held from 16 October 2023 to 22 January 2024. This Field Experience Practice (PPL) will involve carrying out various programs according to what has been previously planned. includes teaching practice, how to prepare the learning process, management and various teacher administration in the form of syllabi, learning plans, learning media, semester programs, annual programs and others that support teaching and learning activities. It is felt that the implementation of the PPL which has been scheduled so far has run smoothly and can be completed well so that the targets that have been set from the start are also achieved. However, the results achieved are not as easy as turning the palm of your hand because there are a few obstacles and obstacles that occur during the implementation of PPL such as a lack of understanding in class control techniques so that the class is not crowded and also delivering material too quickly. However, these obstacles can be overcome by paying more attention by giving questions or warnings directly to students and trying to create learning media that attracts more students' attention, so that their enthusiasm for learning will increase